Beyond Post-Modernism via Polanyi’s Post-Critical Philosophy (The Political Science Reviewer, 2008)
For the last third of the twentieth century on up to the present,we have been increasingly inundated in almost every disciplinewith intellectual work that identifies itself (or is readilyidentifiable) as post-modern, in opposition to now openly questionedassumptions that have characterized the dominant modernintellectual culture (particularly that associated with the EuropeanEnlightenment) for the previous 250 years. What I have inmind when I speak of "post-modern," though, is not just familyresemblances among the contents of this grouping of intellectualwork, despite its great diversity. I wish to speak of post-modernismas an intellectual ethos that has been challenging and progressivelydisplacing the previous intellectual ethos (that of modernism),an ethos that has to do with presuppositions governing theattitudes, methods, and interpersonal relationships of intellectualreflection, discussion, and exchange.